Stress-induced diseases of the thyroid gland in Ukraine during hostilities - Usenko, O. Yu.; Khomenko, I. P.; Kovalenko, A. Ye.; Halochka, I. P.; Kovalchuk, O. I. (Modern medical technology, 2023)
The aim of the study: to analyze and evaluate the relationship between previous life events of a stressful nature in patients who have surgical diseases of the thyroid gland. Materials and methods. We used the questionnaire method (The Life Experiences Survey Irwin G. Sarason, 1978) of patients before planned surgical intervention on the thyroid gland. The number of positive and negative events that happened to patients during the previous year was evaluated. Results. Among individuals, significantly more adverse events were reported by patients with Graves’ disease (128.0 ± 2.3 points) and proliferative hyperthyroid nodular goiter (105.0 ± 1.7 points) compared to patients treated surgically for euthyroid nodular goiter (53.0 ± 0.7 points of negative events) and thyroid carcinomas (62.0 ± 0.8 points of negative events). Conclusions. It has been proven that stress and negative life events can be triggers for dysfunction and development of thyroid gland diseases. Analysis of a patient survey before thyroid surgery indicated a possible relationship between acute stress and the initiation of Graves’ disease and proliferative hyperthyroid nodular goiter.